Aspergillus species of cassava chips in storage in rural areas of southern Cameroon: their relationship with storage duration, moisture content, and processing methods. - Essono , G.G.; Ayodele, M.; Akoa, A.; Foko , J.; Olembo, S.; Gockowski, J. (2007)
A survey was carried out to monitor during a two-month period the incidence of Aspergillus in samples of stored cassava chips traditionally produced in southern Cameroon. Seventy-two samples associated with two forms of chips (cassava balls and cassava pellets) were collected in two locations (Yaoundé and Ebolowa) and 13 Aspergillus species were isolated. In both locations, Aspergillus versicolor was seldom isolated, whereas A. flavus and A. clavatus were most frequently isolated. The level of recovery of isolates obtained was not affected by location and form of chips, but by the duration of storage (P < 0.01) and the moisture content (P < 0.05). Five core species were identified, which formed more than 70% of the total isolates associated with the samples analyzed. These were A. clavatus, A. flavus, A. fumigatus, A. niger and A. ochraceous. Correlation coefficients computed between pairs of these species based on total isolation figures for the two locations showed that some were significantly associated. A. clavatus, A. niger and A. ochraceous were positively related to one another in a significant way. Similarly, significant correlations, positive or negative, were observed between the moisture content and all core Aspergillus species. The larger number of these toxigenic fungi isolated raises concerns on the potential of stored cassava products as a natural substrate liable to mycotoxin formation.